The Meaning and Tasks of Interaction between Society and State by the Example of Law Enforcement Sphere in Russia - PERTRUILOV, Andrey S.; DASHIN, Alexey V.; RASSKAZOV, Leonid P.; RASSKAZOV, Vyacheslav L.; NEDILKO, Yulia V. (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505//jarle.v9 3(33).35, 2018)
In the modern ideas of an ideal legal state, it is compared to the tool of management in the hands of the society, which allows it to organize and consolidate in order to achieve well-being. As a matter of fact, development of such state leads to the crisis of management, caused by the reluctance of government structures to share power and fall under the control of society, on the one hand, and by the society’s unpreparedness both institutionally and culturally, in the other hand. Due to this, studies of interaction between state and society from various sides and in various spheres are very topical. Purpose: Formulating its meaning and main tasks of the activities based on studying the state of normative regulation and practice of interaction between Russian society and the state. Methodology : The authors stay within the dialectic ideology and system of principles and use the general scientific methods of analysis, synthesis, and comparison. Also, the formal and legal and systemic methods are used for working with legal acts. For studying the practical component of interaction between state and society, the authors use the methods of specific sociological studies: observation and survey (personal and questionnaire survey). Also, the statistical method, as well as the method of studying Internet web-site, was used. Results and recommendations: The following conclusions are substantiated: in the regulation of the law enforcement sphere of Russia, the doctrine of state domination has not yet been overcome – which is seen from studying the law and from the practice of its enforcement, despite the fact that these changes are realized by the scientific society and the state; the meaning of interaction between society and state in the law enforcement sphere consists not only in raising the level of public order and safety to a new stage but also in achieving substantial transformation of legal awareness and legal culture of society, making them really civil; on the basis of previous conclusions, the main goal and tasks of interaction between society and state are formulated with the offer for their legislative recognition.